1989
DOI: 10.1099/00207713-39-4-424
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Relatedness among Members of the Genus Frankia

Abstract: The diversity among 43 isolates of the genus Frankia was studied by determining levels of deoxyribonucleic acid relatedness (S1 nuclease method) and DNA base compositions. The guanine + cytosine contents ranged from 66 to 75 mol% . At least nine genomic species were differentiated, including three genomic species among strains compatible with members of the genus Alnus, five genomic species among strains compatible with members of the family Elaeagnaceae, and one genomic species among strains compatible with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
112
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 30 publications
7
112
0
1
Order By: Relevance
“…The second group of Alnus-infective strains (which does not include Alnus-infective, non-nitrogen-fixing strain AgB1-9) (19) is made up of at least three strains, two of which belong to different genomic species (14). This group is not well defined, as indicated by the differences in topology observed with the method which we used, and the data probably reflect the large distances that exist between the strains.…”
Section: Derrnatophilus-congolensismentioning
confidence: 78%
“…The second group of Alnus-infective strains (which does not include Alnus-infective, non-nitrogen-fixing strain AgB1-9) (19) is made up of at least three strains, two of which belong to different genomic species (14). This group is not well defined, as indicated by the differences in topology observed with the method which we used, and the data probably reflect the large distances that exist between the strains.…”
Section: Derrnatophilus-congolensismentioning
confidence: 78%
“…and members of the Myricaceae or by isolates obtained from members of the Casuarinaceae. These LFRFA findings lend weight to the conclusions of Lalonde et al (46), the conclusions of the DNA-DNA relatedness studies (31), and some of the 16s ribosomal DNA sequence data (66) which indicated that the host plant of origin is an important element in defining species. The results of the LFRFA study also confirmed the finding of Nazaret et al (66) that the type strain of "F. alni subsp.…”
mentioning
confidence: 72%
“…In contrast, using a specific PCR-amplified, 268-bp DNA segment of the 16s rRNA gene (E. coli positions 921 to 1189), Nazaret et al (66) compared frankiae representing the nine genomic species of Fernandez et al determined by DNA-DNA relatedness (31). With one exception, the data showed that strains belonging to the same genomic species had identical sequences and that they differed from the other genomic species.…”
mentioning
confidence: 80%
“…This approach used on Frankia isolates yielded at least nine genomic species (10), with three, including F. alni, in the Alnus infectivity group, five in the Elaeagnus infectivity group, and one in the Casuarina infectivity group.…”
mentioning
confidence: 99%
“…In this study, a rapid and reproducible protocol based on DNA amplification and double-strand sequencing of the resulting partial 16S ribosomal DNA (rDNA) sequences was used to estimate the phylogenetic relationships among the genomic species defined by our group (10).…”
mentioning
confidence: 99%